Need and importance of health protection training in Nepal - Simkhada, P; Lee, A; van Teijlingen, E; Karki, K; Neupane, CH (Nepal Journal of Epidemiology, 2015)
By investing in health protection, the health of the nation can be safeguarded from future threats of uncontrolled infectious disease epidemics and disasters. DOI: http://dx.doi.org/10.3126/nje.v5i1.12373